On and off controls within dynein–dynactin on native cargoes - Sanghavi, Paulomi (Proc Natl Acad Sci U S A, 2021)
The dynein–dynactin nanomachine transports cargoes along microtubules in cells. Why dynactin interacts separately with the dynein motor and also with microtubules is hotly debated. Here we disrupted these interactions in a targeted manner on phagosomes extracted from cells, followed by optical trapping to interrogate native dynein–dynactin teams on single phagosomes. Perturbing the dynactin–dynein interaction reduced dynein’s on rate to microtubules. In contrast, perturbing the dynactin–microtubule interaction increased dynein’s off rate markedly when dynein was generating force against the optical trap. The dynactin–microtubule link is therefore required for persistence against load, a finding of importance because disease-relevant mutations in dynein–dynactin are known to interfere with “high-load” functions of dynein in cells. Our findings call attention to a less studied property of dynein–dynactin, namely, its detachment against load, in understanding dynein dysfunction.